The molecule H2 in a strong magnetic field revisited. (May 2021) - Nader, D.J.; Turbiner, A.V.; López Vieyra, J.C.
Highlights: In Born-Oppenheimer approximation of the zeroth order the H2 molecule exists in magnetic field B < 0.178 a.u. in 1 Σ g (ground) state. At magnetic fields 0.178 < B < 12 a.u. the H2 molecule does not exist. At B > 12 a.u. the H2 molecule exists with 3 Π u state as the ground state. 3-term physically adequate trial function allows to describe the H2 molecule in 3 Π u state up to the magnetic fields 10 4 a.u. Abstract: Following the detailed analysis of the H 2 molecule in an intermediate magnetic field B ≲ 5 × 10 8 G performed in Alijah et al, JQSRT 233, 78 (2019) [1] a similar compact, few-parametric, physically adequate, 3-term variational trial function is used to study the energy of the ground state 3 Π u of the hydrogen molecule H 2 in an astronomically strong magnetic field B in the range 5 × 10 10 G ≤ B ≤ 10 13 G. The nuclei (protons) are assumed to be infinitely heavy (Born-Oppenheimer approximation of zeroth order) and situated along the magnetic field line (parallel configuration).